Cytocompatibility of pH-sensitive, chitosan-coated Fe3O4 nanoparticles in gynecological cells - Zhang, Taohong; Wang, Lisha; He, Xinyi; Lu, Hailin; Gao, Li (Frontiers in Medicine, 2022)
Nanoparticles that contact human cells without damaging basic human tissues are becoming more widely used in medicine. Efficient delivery to the intracellular target cell or compartment through the cell membrane must be achieved with minimal cytotoxicity to healthy cells. Fe3O4 nanoparticles have been widely used in biomedical research for their magnetic, non-toxic, and biocompatible properties. However, the effects of Fe3O4 nanoparticles coated with chitosan (CS) on gynecological cells are unclear. In this study, the Fe3O4 nanoparticles were coated with CS to enhance their cytocompatibility and dispersion in water. These CS-Fe3O4 nanoparticles were taken up by gynecological cells and did not affect cell viability in vitro. They have greater cytocompatibility in acidic environments than normal Fe3O4 nanoparticles and have the potential for drug delivery into gynecological cells.